2023
DOI: 10.3390/nu15214507
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis: Prevalence of Non-Alcoholic Fatty Liver Disease and Liver Fibrosis in Patients with Inflammatory Bowel Disease

Pilar Navarro,
Lucía Gutiérrez-Ramírez,
Antonio Tejera-Muñoz
et al.

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is a common concomitant condition in patients with inflammatory bowel disease (IBD). We aim to assess the magnitude of this association. Methods: We searched MEDLINE, EMBASE and Scopus libraries for the period up to February 2023 to identify studies reporting cohorts of IBD patients in which NALFLD was evaluated. Results: Eighty-nine studies were analyzed. The overall prevalence of NAFLD was 24.4% (95%CI, 19.3–29.8) in IBD, 20.2% (18.3–22.3) in Crohn’s dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…The prevalence of liver fibrosis in the IBD population varies in different studies, reaching up to 16.7% [ 24 ], and there is some evidence revealing higher percentages among NAFLD patients with IBD compared to those without IBD [ 25 , 26 ]. In the aforementioned retrospective American study by Ritaccio et al, liver fibrosis was assessed non-invasively through the NALFD fibrosis score (NFS), which includes age, body mass index, diabetes, platelet count, transaminase levels and serum albumin.…”
Section: Nafld Clinical Course In Ibd Patientsmentioning
confidence: 99%
“…The prevalence of liver fibrosis in the IBD population varies in different studies, reaching up to 16.7% [ 24 ], and there is some evidence revealing higher percentages among NAFLD patients with IBD compared to those without IBD [ 25 , 26 ]. In the aforementioned retrospective American study by Ritaccio et al, liver fibrosis was assessed non-invasively through the NALFD fibrosis score (NFS), which includes age, body mass index, diabetes, platelet count, transaminase levels and serum albumin.…”
Section: Nafld Clinical Course In Ibd Patientsmentioning
confidence: 99%
“…The prevalence of NAFLD in the general population has increased significantly over time, from 25.5% before 2005 to 37.8% in 2016 or later [11]. A recent epidemiologic study investigating the occurrence of hepatobiliary conditions in IBD patients revealed a median 26% prevalence of NAFLD [12,13]. Crucially, patients with IBD exhibit an elevated rate of NAFLD diagnosis independent of traditional metabolic risk factors, such as obesity and diabetes [14].…”
Section: Introductionmentioning
confidence: 99%